Solve the following equations:
$\dfrac{{{x^3} + 1}}{{{x^2} - 1}} = x + \sqrt {\dfrac{6}{x}} .$
Answer
Verified
513.6k+ views
Hint: - Use \[{{\text{a}}^3} + {b^3} = \left( {a + b} \right)\left( {{a^2} + {b^2} - ab} \right)\], \[\left( {{a^2} - {b^2}} \right) = \left( {a - b} \right)\left( {a + b} \right)\]
As we know \[{{\text{a}}^3} + {b^3} = \left( {a + b} \right)\left( {{a^2} + {b^2} - ab} \right)\], and \[\left( {{a^2} - {b^2}} \right) = \left( {a - b} \right)\left( {a + b} \right)\]
So, apply these properties
\[
\Rightarrow \dfrac{{{x^3} + 1}}{{{x^2} - 1}} = x + \sqrt {\dfrac{6}{x}} . \\
\Rightarrow \dfrac{{\left( {x + 1} \right)\left( {{x^2} + 1 - x} \right)}}{{\left( {x - 1} \right)\left( {x + 1} \right)}} = x + \sqrt {\dfrac{6}{x}} \\
\]
\[ \Rightarrow \left( {x + 1} \right)\]Is canceled out from the numerator and denominator.
\[
\Rightarrow \dfrac{{\left( {{x^2} + 1 - x} \right)}}{{\left( {x - 1} \right)}} = x + \sqrt {\dfrac{6}{x}} \\
\Rightarrow \dfrac{{\left( {{x^2} + 1 - x} \right)}}{{\left( {x - 1} \right)}} - x = \sqrt {\dfrac{6}{x}} \Rightarrow \dfrac{{\left( {{x^2} + 1 - x} \right) - {x^2} + x}}{{x - 1}} = \sqrt {\dfrac{6}{x}} \Rightarrow \dfrac{1}{{x - 1}} = \sqrt {\dfrac{6}{x}} \\
\]
By, cross multiplication
\[ \Rightarrow 1 \times \sqrt x = \left( {x - 1} \right)\sqrt 6 \]
Now, squaring on both sides
\[
\Rightarrow {\left( {\sqrt x } \right)^2} = {\left( {x - 1} \right)^2}{\left( {\sqrt 6 } \right)^2} \Rightarrow x = 6\left( {{x^2} + 1 - 2x} \right) \\
\Rightarrow 6{x^2} - 13x + 6 = 0 \\
\Rightarrow 6{x^2} - 9x - 4x + 6 = 0 \\
\Rightarrow 3x\left( {2x - 3} \right) - 2\left( {2x - 3} \right) = 0 \\
\Rightarrow \left( {2x - 3} \right)\left( {3x - 2} \right) = 0 \\
\Rightarrow \left( {2x - 3} \right) = 0{\text{, and }}\left( {3x - 2} \right) = 0 \\
\Rightarrow x = \dfrac{3}{2},{\text{ and }}x = \dfrac{2}{3} \\
\]
So, this is the required answer.
Note: -In such types of questions always remember the basic formulas which are stated above then after cross multiplication factorize the equation and simplify the equation we will get the required solution of the equation.
As we know \[{{\text{a}}^3} + {b^3} = \left( {a + b} \right)\left( {{a^2} + {b^2} - ab} \right)\], and \[\left( {{a^2} - {b^2}} \right) = \left( {a - b} \right)\left( {a + b} \right)\]
So, apply these properties
\[
\Rightarrow \dfrac{{{x^3} + 1}}{{{x^2} - 1}} = x + \sqrt {\dfrac{6}{x}} . \\
\Rightarrow \dfrac{{\left( {x + 1} \right)\left( {{x^2} + 1 - x} \right)}}{{\left( {x - 1} \right)\left( {x + 1} \right)}} = x + \sqrt {\dfrac{6}{x}} \\
\]
\[ \Rightarrow \left( {x + 1} \right)\]Is canceled out from the numerator and denominator.
\[
\Rightarrow \dfrac{{\left( {{x^2} + 1 - x} \right)}}{{\left( {x - 1} \right)}} = x + \sqrt {\dfrac{6}{x}} \\
\Rightarrow \dfrac{{\left( {{x^2} + 1 - x} \right)}}{{\left( {x - 1} \right)}} - x = \sqrt {\dfrac{6}{x}} \Rightarrow \dfrac{{\left( {{x^2} + 1 - x} \right) - {x^2} + x}}{{x - 1}} = \sqrt {\dfrac{6}{x}} \Rightarrow \dfrac{1}{{x - 1}} = \sqrt {\dfrac{6}{x}} \\
\]
By, cross multiplication
\[ \Rightarrow 1 \times \sqrt x = \left( {x - 1} \right)\sqrt 6 \]
Now, squaring on both sides
\[
\Rightarrow {\left( {\sqrt x } \right)^2} = {\left( {x - 1} \right)^2}{\left( {\sqrt 6 } \right)^2} \Rightarrow x = 6\left( {{x^2} + 1 - 2x} \right) \\
\Rightarrow 6{x^2} - 13x + 6 = 0 \\
\Rightarrow 6{x^2} - 9x - 4x + 6 = 0 \\
\Rightarrow 3x\left( {2x - 3} \right) - 2\left( {2x - 3} \right) = 0 \\
\Rightarrow \left( {2x - 3} \right)\left( {3x - 2} \right) = 0 \\
\Rightarrow \left( {2x - 3} \right) = 0{\text{, and }}\left( {3x - 2} \right) = 0 \\
\Rightarrow x = \dfrac{3}{2},{\text{ and }}x = \dfrac{2}{3} \\
\]
So, this is the required answer.
Note: -In such types of questions always remember the basic formulas which are stated above then after cross multiplication factorize the equation and simplify the equation we will get the required solution of the equation.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE